Strategi Penyaluran Dana Zakat Produktif Melalui Program Pemberdayaan Ekonomi - Siti Khiyarotus Sholikhah; Mansur Efendi (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2022)
Poverty is a serious problem, not only in big cities but also in all corners of the country. LAZIS Central Java Solo Branch is here to help the community distribute their zakat to mustaḥiq and also help small entrepreneurs to develop their businesses from the zakat funds that have been collected. This study aims to explain the strategy for channeling productive zakat funds through an economic empowerment program and to mention the supporting and inhibiting factors in distributing productive zakat funds at LAZIS Central Java, Solo Branch. This study used a descriptive qualitative approach with a type of fieldresearch. The data sources used are primary and secondary data sources. Primary data sources were obtained from observations and interviews conducted with Central Java LAZIS management and  mustaḥiq, and secondary data sources were obtained from important supporting documents. The results of this study indicate that the strategy applied in channeling productive zakat funds for the LAZIS Central Java Economic Empowerment Program, Solo Branch, uses the stages of survey, submission of files, verification, rolling out and mentoring. Factors supporting the distribution of productive zakat funds consist of four factors, namely the existence of a clear program design, the availability of zakat funds, the presence of volunteers who participate and the level of participation of beneficiaries. While the inhibiting factors consist of two factors, namely the lack of quality human resources and the lack of maximum performance in the process of monitoring or program monitoring.